Development and sector labor income shares - Daniel Schäfer (Johannes Kepler University of Linz, Department of Economics, 2024)
The development accounting literature assumes that sector labor income shares and output per person across countries are not correlated. In this paper, I show that the data reject this assumption for a large set of countries. The labor shares in the manufacturing and the market-services sectors increase significantly more with output per person than in other sectors, leading to a shift of labor income across sectors with economic development. The empirical evidence suggests that capital deepening is the primary driver of these patterns. Researchers can directly use the new dataset of labor shares to calibrate multisector models.
Keywords: E01; E25; O11; 330; Capital intensity; Economic development; Input-output tables; Multisector models; Sector development accounting